Comparison of disinfection by-products formed by preoxidation of sulfamethazine by K2FeO4 and O3 and the influence on cytotoxicity and biological toxicity - Li, Siwen; Lin, Yingzi; Wang, Gaoqi; Zhu, Suiyi; Liu, Gen; Shi, Chunyan; Chen, Lei (Frontiers in Chemistry, 2022)
This study researched the formation of disinfection by-products (DBPs) in sulfamethazine (SMZ) chlorination after preoxidation by K2FeO4 and O3 and the influence of preoxidation on cytotoxicity and biological toxicity. Then, the study emphatically analyzed the influencing factors such as NaClO dosage, pH value, reaction temperature, fulvic acid (FA), and bromide and iodide ions. The results showed that preoxidation by K2FeO4 effectively inhibited the formation of DBPs of haloketones (HKS) and trihalomethanes (THMs), with an average inhibition rate of over 60%. The formation of DBPs after preoxidation by O3 was higher than that by K2FeO4; preoxidation by K2FeO4 reduced the influence of NaClO dosage, temperature, and pH value on the production of DBPs after SMZ chlorination. The cytotoxicity and biological toxicity of SMZ chlorination after preoxidation were evaluated and compared by calculating the LC50 value of DBPs and the luminescent bacteria method. The results of both calculation methods showed that the toxicity of DBPs after preoxidation by K2FeO4 was lower than that by O3 preoxidation. K2FeO4 and O3 preoxidation improved the SMZ removal efficiency by 8.41 and 10.49%, respectively, and inhibited the formation of most DBPs, but the preoxidation promoted the formation of highly toxic DBPs (HANs). The toxicity of DBPs formed in SMZ chlorination after preoxidation by K2FeO4 and O3 was slightly higher than that of chlorination disinfection alone, but it was still within the safe range. This study provides more new details about the formation and toxicity changes of DBPs in the process of SMZ chlorination after preoxidation.